Influence of films /TV series/ TV programs on tourist’s motivation to travel - Baltekenova, M.; Doszhanova, U.; Bulkanova, A.; Oralbek, M. (Submitted in partial fulfillment of the requirements for the degree of Bachelor of Service Management In Tourism M. S. Narikbayev KAZGUU University School of Liberal Arts, 2021)
Modern tourists are in search of new experiences, and therefore they are looking for new directions in tourism in order to satisfy their travel needs. Film tourism has become one of these topical areas, which implies the phenomenon of the influence of television content on the motivation of viewers to travel. Recent studies indicate that in this way, films, series and television programs are able to generate tourism income in a country or in a specific area. However, academic articles and studies on this topic about our country are limited, and therefore the purpose of this study was to analyze from different angles the impact of the television platform on the motivation to visit Kazakhstan. According to three selection criteria, namely high recognition, the presence of foreign awards, as well as the promotion of Kazakh culture, cases about TV program stars, such as Dimash Kudaibergenov and group 91; the film "Borat"; as well as the Kazakh music video “Medina” were selected as the objects of study. In this paper, the cases were analyzed on the basis of news portals, interviews, published articles, statistics on social networks, etc. Based on these data, it was concluded that TV-induced tourism in Kazakhstan has great potential but requires support and development.
Keywords: tourism; Film tourism; television content; Kazakh culture